3 Cases of Inflicted Skull Crush Injuries in Infants. Issue 12 (December 2021) - Brown, Emily C.B.; Donaruma-Kwoh, Marcella M.; Otjen, Jeffrey P.; Feldman, Kenneth W.
Abstract : Abstract: We describe 3 infants with skull fractures that involved more than 1 skull bone. On further evaluation, 2 of the 3 infants had additional fractures at other sites of the body and the third infant had concerning bruising of the face. Although an accidental mechanism of injury was initially given as the history in each case, law enforcement investigations led all 3 fathers to confess to crushing their infants' skulls out of frustration. These crushes were caused by their arms or hands. Bilateral skull fractures or those involving more than 1 skull bone can be seen in falls as well as in crush injuries. A crush-like pattern of injury, in the absence of a clear and plausible accidental mechanism, should raise concerns for possible physical abuse especially in nonambulatory infants.